Svartedalens naturreservat : en social rikedom värd att utveckla! - Göransson, Tony (SLU/Dept. of Silviculture, 2005)
Svartedalens nature reserve a social richness worth develop. The nature reserve of Svartedalen is an area of high biological and social values. The reserve is located close to several densely populated areas. The reserve has been classified as a national area of interest for nature conservation and outdoor life, and as a Natura 2000 area according to both the bird- and habitat directions. The reserve is the largest landarea in Västra Götaland, 3 410 hectares, where a resolution has been made about all these forms of protection. The foundation Skogssällskapet owns 1 956 hectares of the reserve, at 1 384 hectares of the property they pursue FSC-certified silver culture, according to current management plan. Västkuststiftelsen is the administrator of the reserve. To calculate how much the restrictions for the reserve have an effect on the economic result for the forestry, a comparison is made between two similar forest properties where FSC-certified silver culture is practised. The yearly economic result from the forestry in the nature reserve of Svartedalen are, 256 000 SEK or 186 SEK per hectare, calculated on means of the last five year result. When Skogssällskapet acquired the property of Svartedalen their purpose was to develop and create opportunities for a multiple use of the forest. The conditions have been changed and the purpose hasn't been fulfilled. To get an apprehension of the costs relation to the value of the non-monetary value in the nature reserve, the non-monetary value has been quantified according to a method which has been used in similar studies. Costs in form of receipts that did not occur from the forestry, has been compared with the result from the recreation value. The result from these comparison shows that the biggest public welfare obtains from taking care of the non-monetary value in the reserve. The calculated recreation value has a interval between 418 000 SEK and 27 600 000 SEK a year. Within the social value that the forest has it is possible to distinguish seven different adventure values according to a report from Regionplane and trafikkontoret in Stockholm. The method is used in analysing Svartedalens nature reserve. The results show the area and number of the adventure value. Last is discussed how the reserves different values can be taken care of and saved in the best way for the future. The ownership has an impact on how the value in the reserve is take care of. In Svartedalens nature reserve the public welfare value is bigger then the economic result from a forestry whit normal yield. It is stated that taking care of the public welfare in the reserve, is depending on the owners purpose. A public owner's purpose is better suited, than a private, to take care of the total public welfare values in Svartedalens nature reserve.